1995
DOI: 10.1111/j.1476-5381.1995.tb13307.x
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of antidepressant drugs with central and peripheral (enteric) 5‐HT3 and 5‐HT4 receptors

Abstract: 1 A combined study of receptor binding in central neuronal cell membranes and functional responses in isolated segments of guinea-pig small intestine allowed characterization of the interaction of four antidepressant drugs with central and peripheral 5-HT3 and 5-HT4 receptors. 3 In whole ileal segments, concentration-response curves to 5-HT were biphasic, with the high-and low-potency phases involving 5-HT4 and 5-HT3 receptors, respectively. Curves to 2-methyl-5-hydroxytryptamine (2-methyl-5-HT: a 5-HT3 recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Fluoxetine blocks different types of nAcChoRs with different strengths, and these effects show some similarities with the action of fluoxetine on 5HT 3 receptors (25)(26)(27). Thus, fluoxetine inhibits the membrane currents elicited by activation of both muscle (␣ 1 ␤ 1 ␥␦) and neuronal (␣ 2 ␤ 4 or ␣ 3 ␤ 4 ) nAcChoRs, either by increasing the rate of receptor desensitization and͞or by inducing channel blockage, which may indirectly facilitate the desensitizing state of the receptor.…”
Section: Discussionmentioning
confidence: 93%
“…Fluoxetine blocks different types of nAcChoRs with different strengths, and these effects show some similarities with the action of fluoxetine on 5HT 3 receptors (25)(26)(27). Thus, fluoxetine inhibits the membrane currents elicited by activation of both muscle (␣ 1 ␤ 1 ␥␦) and neuronal (␣ 2 ␤ 4 or ␣ 3 ␤ 4 ) nAcChoRs, either by increasing the rate of receptor desensitization and͞or by inducing channel blockage, which may indirectly facilitate the desensitizing state of the receptor.…”
Section: Discussionmentioning
confidence: 93%
“…Using the NIMH Psychoactive Drug Screening Program database, we did not find any study looking at the binding affinity of fluoxetine at the mouse 5-HT 4 receptor. The only study looking at binding affinities of fluoxetine for serotoninergic receptor demonstrated negligible binding of fluoxetine to the 5-HT 4 receptor in pig striatal membranes (Lucchelli et al, 1995). In addition, quantitative autoradiography revealed that the binding of the 5-HT 4 receptor ligand [ 3 H]GR113808 was not significantly changed in fluoxetine-treated mice (Kobayashi et al, 2012).…”
Section: Requirement Of 5-ht 4 Receptors For the Behavioral And Neuromentioning
confidence: 99%
“…It is generally believed that fluoxetine exerts its therapeutic effects by enhancing serotonergic transmission, exclusively through inhibition of serotonin (5-hydroxytryptamine; 5HT) transporters with minimal or no effects on other neurotransmitter receptors (1,2). However, it has been shown that fluoxetine inhibits 5HT binding in the choroid plexus (3), that it appears to be an agonist of 5HT 2C receptors in cultured astrocytes (4), and that it inhibits currents mediated by 5HT 3 receptors in rat nodose ganglion neurons (5), as well as the binding of 5HT to 5HT 3 and 5HT 4 receptors (6). In addition, chronic treatment of fluoxetine may cause a down-regulation of 5HT 1 receptors (2) and also alter the expression of other receptors, although the latter effects are somewhat controversial (7).…”
mentioning
confidence: 99%